AMDB – An Approach for Sharing Mobile Databases - Moraes Filho, José de Aguiar; Brayner, Angelo (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2004)
We define a Mobile Database Community (MDBC) as a dynamic collection of autonomous mobile databases in which each database user can access databases in the community through a wireless communication infrastructure. New participants may join to an MDBC as they move within communication range of one or more hosts which are members of the MDBC. MDBC participants may also transiently disconnect from the network due to communication disruptions or to save power. This paper describes an agent-based architecture, called AMDB (Accessing Mobile Databases), which enables such communities to be formed opportunistically over mobile database hosts in ad hoc configurable environments. The AMDB architecture is fully distributed and exploits physical mobility of hosts and logical mobility of database queries and their results across mobile hosts.